The Impact of Local Revenue, Regional Balance, Expenditure, and Financing on Economic Growth - Harnovinsah Harnovinsah; Yananto Mihadi Putra; Zamri Ahmad (Social and Economic Bulletin, 2024)
The research aims to know the Locally Generated Revenue (PAD), Balancing Fund (DP), Local Government Expenditures (BD) and Regional Financing (PD) of Regional Economic Growth (PDRB). The data used in this study is annual data published by website Directorate General of Fiscal Balance and Central Bureau of Statistics for five period from 2011 until 2015. The analytical method used is Multiple Linear Regression. The results showed that the Locally Generated Revenue (PAD), Local Government Expenditures (BD) and Regional Financing (PD) has no effect significant on Regional Economic Growth (PDRB). While Balancing Fund (DP) has negatively significant effect on Regional Economic Growth (PDRB).